Durable Solution: Right to Education a Hope for Better Future for Refugees - Ummer Bashir; Munira T. (East Asian Journal of Multidisciplinary Research, 2022)
Globally, after the World War 2, the population of displaced people is at its highest. Significant, long-lasting, and impacting several facets of human existence, the repercussions of forcible relocation are substantial and far-reaching. Education is a crucial issue that is significantly impacted by the forced migration. Since 2010, education has been among the United Nations Refugee Agency’s worldwide strategic goals (UNHCR). For refugees, the optimism and aspiration for an education that would allow them to attain secure and decent careers has been a fundamental aspect of their lives. The purpose of this article is to examine the refugee’s right to education and to define the nation’s human rights duties in educational affairs focusing on the present flow of refugees.